Photo-thermal hydrophobic coating and application thereof on asphalt pavement

By spraying photothermal hydrophobic coatings made of materials such as multi-wall carbon nanotubes, titanium dioxide and lauric acid on asphalt pavement, the problem of poor anti-icing effect in the existing technology at extremely low temperatures is solved, and the all-weather anti-icing and de-icing functions are achieved, and the cost and curing time are reduced.

CN119592109APending Publication Date: 2025-03-11CHONGQING DIDA IND TECH RES INST CO LTD

Patent Information

Application Number
CN202411649946.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-19
Publication Date
2025-03-11

AI Technical Summary

Technical Problem

The existing hydrophobic coating has significantly reduced the anti-icing effect in extremely low temperature environments, and the common base material is high in cost and has a long curing time, which affects traffic.

Method used

Photothermal hydrophobic coatings are made of multi-wall carbon nanotubes, titanium dioxide and lauric acid. By spraying them on asphalt pavement, anti-ice coating is formed, and solar energy is used to suppress road icing and accelerate icing melting.

Benefits of technology

In extreme low temperature environments, it significantly delays the icing of water surface, has all-weather anti-icing and de-icing functions, improves deicing efficiency, reduces energy consumption, and has low cost of base materials and short curing time.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119592109A_ABST
    Figure CN119592109A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of coatings, in particular to a photo-thermal hydrophobic coating and application thereof on an asphalt pavement. The photo-thermal hydrophobic coating is prepared from the following raw materials in parts by weight: 1 to 1.5 parts of multiwalled carbon nanotubes, 3 to 4 parts of titanium dioxide, 6 to 7 parts of lauric acid and 100 parts of absolute ethyl alcohol. The anti-icing coating with a rough surface is constructed on the road surface by using the multi-walled carbon nanotubes, titanium dioxide and lauric acid, the anti-icing coating has hydrophobic anti-icing performance and photo-thermal anti-icing performance at the same time, and the effects of inhibiting the formation of road icing and accelerating the thawing of the road icing can be achieved by fully utilizing solar energy. In an extremely low-temperature environment, the coating still can obviously delay the icing of water on the surface of the coating, and has good anti-icing performance; under the condition of weak light, the hydrophobicity of the coating can still play an ice inhibiting role, and all-weather anti-icing and deicing are achieved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of coatings, and in particular to a photothermal hydrophobic coating and application thereof on asphalt pavement. Background Art

[0002] Road icing is usually the main reason for frequent traffic accidents and reduced road performance in winter. On the one hand, snow on the road is prone to ice after being compacted by vehicle loads, which reduces the friction coefficient between vehicle tires and the road surface. On the other hand, the meltwater formed by the melting of snow on the road will penetrate into the road surface, shrink and expand in volume with the change of temperature difference between day and night, causing damage to the road surface structure and affecting the performance of the road surface.

[0003] Traditional deicing methods, such as using deicing vehicles and salt spraying, often damage road structures and seriously pollute the surrounding environment. In recent years, active anti-icing and deicing methods have begun to enter the public eye. In nature, the surfaces of plants and animals such as lotus leaves and butterfly wings show hydrophobicity. On this basis, people try to construct hydrophobic structures on the road surface to prevent water droplets from staying on their surface, thereby delaying the freezing time of water droplets on the road surface and reducing the adhesion of the ice layer on the road surface. However, relevant studies have found that in extremely low temperature environments, the anti-icing effect of the hydrophobic coating will be significantly reduced. In addition, common hydrophobic coating base materials (such as epoxy resins) are often expensive, and the curing time at room temperature is often more than 24 hours, which seriously affects traffic. Therefore, it is necessary to make certain improvements and optimizations to the hydrophobic coating so that it can still play an anti-icing role under extremely low temperature conditions. Summary of the invention

[0004] The purpose of the present invention is to propose a photothermal hydrophobic coating and its application on asphalt pavement in view of the above-mentioned deficiencies in the prior art.

[0005] A photothermal hydrophobic coating of the present invention comprises the following raw materials in parts by weight:

[0006] 1-1.5 parts of multi-walled carbon nanotubes, 3-4 parts of titanium dioxide, 6-7 parts of lauric acid, and 100 parts of anhydrous ethanol.

[0007] Furthermore, the inner diameter of the multi-walled carbon nanotube is 3-5 nm, the outer diameter is 8-15 nm, and the length is 3-12 μm.

[0008] Furthermore, the average particle size of the titanium dioxide is 50 nm and the specific surface area is 60-70 m 2 / g.

[0009] Furthermore, the pH of the lauric acid is 6.5-7 and the density is 1.05 g / cm 3 .

[0010] Furthermore, the mass ratio of multi-walled carbon nanotubes, titanium dioxide and lauric acid is 1:3:5.

[0011] An application of the above-mentioned photothermal hydrophobic coating on an asphalt pavement is to weigh multi-walled carbon nanotubes, titanium dioxide and lauric acid, mix them evenly with anhydrous ethanol to obtain the coating, and then spray the coating on the asphalt cured layer of the pavement to form an anti-icing coating.

[0012] Furthermore, the coating spraying volume is 90-110mL / m 2 .

[0013] Furthermore, the emulsified asphalt is coated on the roadbed and solidified to form the asphalt solidification layer.

[0014] Furthermore, the preparation method of the emulsified asphalt is: mixing water, a nonionic emulsifier and anhydrous calcium chloride to prepare a soap solution, and preheating the base asphalt to 100-120° C. and then mixing and stirring with the soap solution.

[0015] Furthermore, the mass ratio of base asphalt, water, nonionic emulsifier and anhydrous calcium chloride is 100:70:3:0.1.

[0016] Compared with the prior art, the present invention has the following beneficial effects:

[0017] 1. The present invention uses multi-walled carbon nanotubes, titanium dioxide and lauric acid to construct an anti-icing coating with a rough surface on the road surface. It has both hydrophobic and photothermal anti-icing properties, and can make full use of solar energy to inhibit the formation of road ice and accelerate the melting of road ice. In an extremely low temperature environment, the coating can still significantly delay the freezing of water on its surface and has good anti-icing performance; in the case of weak light, the hydrophobicity of the coating can continue to play an ice-suppressing function, achieving all-weather anti-icing and de-icing;

[0018] 2. The photothermal super-hydrophobic anti-icing coating prepared by the present invention has significant wave absorption characteristics. When the microwave heating method is used for road deicing, the deicing efficiency can be significantly improved and the energy consumption can be reduced.

[0019] 3. The photothermal hydrophobic anti-icing coating described in the present invention has a base material of emulsified asphalt. Emulsified asphalt has a low cost and is suitable for paving on a large area of ​​the road. At the same time, emulsified asphalt has a short curing time, which is convenient for rapid construction and has little impact on traffic. BRIEF DESCRIPTION OF THE DRAWINGS

[0020] Figure 1 The three-dimensional morphology of the multi-walled carbon nano-modified coating, titanium dioxide modified coating and photothermal hydrophobic coating 4;

[0021] Figure 2 is a thermal imaging image of the photothermal hydrophobic coating 4 under near-infrared light irradiation;

[0022] Figure 3 FTIR spectra of titanium dioxide modified coating and photothermal hydrophobic coating 4. DETAILED DESCRIPTION

[0023] The following are specific embodiments of the present invention and the accompanying drawings to further describe the technical solution of the present invention, but the present invention is not limited to these embodiments.

[0024] Example 1

[0025] Photothermal hydrophobic coating is prepared using photothermal hydrophobic coating.

[0026] The multi-walled carbon nanotubes, titanium dioxide and lauric acid are weighed and evenly mixed with anhydrous ethanol to obtain a coating.

[0027] Apply emulsified asphalt on the surface of the glass slide;

[0028] When the emulsified asphalt is about to solidify, the coating is sprayed on its surface using a high-pressure spray gun at a pressure of 2.0 MPa. The coating cycle is repeated three times and then dried in a ventilated laboratory environment for one day to obtain a photothermal hydrophobic coating. The spraying amount of the coating is 100 mL / m 2 .

[0029] The mass ratio of multi-walled carbon nanotubes, titanium dioxide and lauric acid is 1:3:2, and a photothermal hydrophobic coating 1 is prepared.

[0030] The mass ratio of multi-walled carbon nanotubes, titanium dioxide and lauric acid is 1:3:3, and the photothermal hydrophobic coating 2 is prepared.

[0031] The mass ratio of multi-walled carbon nanotubes, titanium dioxide and lauric acid is 1:3:4, and a photothermal hydrophobic coating 3 is prepared.

[0032] The mass ratio of multi-walled carbon nanotubes, titanium dioxide and lauric acid is 1:3:5 to prepare a photothermal hydrophobic coating 4.

[0033] The mass ratio of multi-walled carbon nanotubes, titanium dioxide and lauric acid is 1:3:6, and a photothermal hydrophobic coating 5 is prepared.

[0034] Comparative Example 1

[0035] One part of multi-walled carbon nanotubes and 100 parts of anhydrous ethanol are evenly mixed to obtain a coating.

[0036] The other aspects are the same as those in Example 1, to obtain a multi-walled carbon nanotube modified coating.

[0037] Comparative Example 2

[0038] The coating was obtained by uniformly mixing 3 parts of titanium dioxide with 100 parts of anhydrous ethanol.

[0039] The rest is the same as in Example 1, and a titanium dioxide modified coating is obtained.

[0040] Comparative Example 3

[0041] One part of multi-walled carbon nanotubes, 5 parts of lauric acid and 100 parts of anhydrous ethanol are uniformly mixed to obtain a coating.

[0042] The other parts are the same as those in Example 1, namely, multi-walled carbon nanotubes\lauric acid modified coating.

[0043] Comparative Example 4

[0044] 3 parts of titanium dioxide, 5 parts of lauric acid and 100 parts of anhydrous ethanol are uniformly mixed to obtain a coating.

[0045] The rest is the same as in Example 1, and a titanium dioxide\lauric acid modified coating is obtained.

[0046] Example 2

[0047] A method for preparing an anti-icing coating for an asphalt pavement, the specific steps are as follows:

[0048] Step 1: Weigh multi-walled carbon nanotubes, titanium dioxide and lauric acid, and mix them evenly with anhydrous ethanol to obtain a coating. The mass ratio of multi-walled carbon nanotubes, titanium dioxide and lauric acid is 1:3:2;

[0049] Step 2: Apply emulsified asphalt on the surface where the Marshall specimen is required;

[0050] Step 3: When the emulsified asphalt is about to solidify, use a spray gun to evenly spray the paint on its surface. The spraying amount of the paint is 100mL / m 2 .

[0051] The mass ratio of multi-walled carbon nanotubes, titanium dioxide and lauric acid is 1:3:2, and an asphalt pavement anti-icing coating 1 is prepared.

[0052] The mass ratio of multi-walled carbon nanotubes, titanium dioxide and lauric acid is 1:3:3, and an asphalt pavement anti-icing coating 2 is prepared.

[0053] The mass ratio of multi-walled carbon nanotubes, titanium dioxide and lauric acid is 1:3:4, and an asphalt pavement anti-icing coating 3 is prepared.

[0054] The mass ratio of multi-walled carbon nanotubes, titanium dioxide and lauric acid is 1:3:5, and an anti-icing coating 4 for an asphalt pavement is prepared.

[0055] The mass ratio of multi-walled carbon nanotubes, titanium dioxide and lauric acid is 1:3:6, and an anti-icing coating 5 for an asphalt pavement is prepared.

[0056] Comparative Example 5

[0057] 3 parts of titanium dioxide, 5 parts of lauric acid and 100 parts of anhydrous ethanol are uniformly mixed to obtain a coating.

[0058] The rest is the same as in Example 2 to prepare an asphalt pavement anti-icing coating 6.

[0059] The photothermal hydrophobic coatings 1-5 prepared in Example 1 were tested for hydrophobicity, and the specific performance tests are as follows:

[0060] The contact angle and rolling angle of the water droplet with the photothermal hydrophobic coating prepared in Example 1 were measured by using an SDC 100 optical contact angle meter and a GFSG6035 manual angle stage. The results are as follows:

[0061] Table 1 Comparison table of coating hydrophobicity test results

[0062]

[0063] From the results in Table 1, it can be seen that increasing the mass ratio of lauric acid in the coating composition can significantly improve the hydrophobicity of the coating; however, when the mass ratio of lauric acid to titanium dioxide exceeds 5:3, the hydrophobicity of the coating is not significantly improved. Therefore, when the mass ratio of lauric acid to titanium dioxide is determined to be 5:3, the corresponding ratio is the optimal composition of the coating. Based on this result, subsequent experiments were all conducted with photothermal hydrophobic coating 4 as the test object.

[0064] The contact angle and rolling angle of water droplets with the photothermal hydrophobic coating 4 and the coatings prepared in comparative examples 1-4 were measured by using an SDC 100 optical contact angle meter and a GFSG6035 manual angle stage. The results are as follows:

[0065] Table 2 Comparison table of coating hydrophobicity test results

[0066]

[0067] From the results in Tables 1 and 2, we can see that multi-walled carbon nanotubes have a certain degree of hydrophobicity and titanium dioxide has hydrophilicity. The effect of modifying the coating with a single material is not significant. After adding lauric acid, the hydrophobicity of the coating is significantly improved, reaching the super-hydrophobic requirement. During the experiment, we found that when the ratio of multi-walled carbon nanotubes, titanium dioxide and lauric acid is 1:3:5, the hydrophobic performance of the coating reaches the best.

[0068] Figure 1 The three-dimensional morphology of multi-walled carbon nanotube modified coating, titanium dioxide modified coating and photothermal hydrophobic coating 4 is shown (from left to right). Through comparative analysis, we can see that the root mean square roughness (Rq) values ​​of multi-walled carbon nanotube modified coating and titanium dioxide modified coating are similar, which are 5.574μm and 6.241μm respectively. When carbon nanotubes, titanium dioxide and lauric acid are mixed at 100ml / m 2When mixed with a spraying amount of , the Rq value of the coating was significantly increased to 9.673 μm, which is 1.7 times that of the multi-walled carbon nano-modified coating.

[0069] According to the Cassie-Baxter model, a rough surface may not be fully wetted by the liquid, but rather an air layer is formed between the surface and the liquid. This air layer reduces the contact area between the liquid and the solid surface, potentially enhancing the hydrophobicity of the coating. Our experimental results support this model, indicating that the hydrophobicity of the MWCNT / TiO2 / lauric acid modified emulsified asphalt coating can be effectively enhanced by increasing its surface roughness.

[0070] The photothermal hydrophobic coating 4 uses a thermal imager to record the temperature rise of the coating surface under near-infrared light irradiation, and the results are as follows.

[0071] Figure 2 This is a thermal image of the photothermal hydrophobic coating 4 under near-infrared light. After 60 seconds of illumination, the surface temperature of the coating increased from -10°C to 4.6°C. This shows that under natural light, the coating can inhibit road icing in an environment below zero degrees. At the same time, in a higher temperature environment, the temperature rise of the coating due to light and heat will not soften the asphalt, resulting in reduced road performance.

[0072] Figure 3 The FTIR spectra of Comparative Example 4 and Photothermal Hydrophobic Coating 4 are shown, showing 1563 cm -1 and 1605cm -1 The significant absorption peak at , which is caused by the C=O bond in the coating. Figure 3 In (b), at 1713 cm -1 and 1737cm -1 A new characteristic peak was observed at , which was caused by the C=C bond introduced by multi-walled carbon nanotubes. Figure 3 By integrating the spectrum, the areas of characteristic peaks S1=44.1 and S2=132.6 caused by conjugated double bonds in different coatings can be determined (S1=44.1 and S2=132.6). It can be seen that after the introduction of multi-walled carbon nanotubes, the number of conjugated double bonds increased significantly and the conjugation effect was significantly enhanced. The delocalization of π electrons increased significantly, reducing the energy difference between different energy levels and the energy required for transition, thereby enhancing the photothermal effect of the coating.

[0073] The temperature change and deicing condition of the titanium dioxide / lauric acid modified coating prepared by the photothermal hydrophobic coating 4 and the comparative example 4 were tested using an 800W Supor household microwave oven after microwave heating.

[0074] Table 3 Comparison of specimen surface temperature under different microwave radiation time

[0075]

[0076] It can be seen that in the microwave heating test, after 180s of microwave heating, the temperature of the standard Marshall sample increased by 10.8℃, while the temperature of the Marshall sample coated with the asphalt pavement anti-icing coating 6 increased by 12.7℃, and the temperature of the Marshall sample coated with the photothermal hydrophobic coating 4 increased by 13.9℃. After the heating time was extended to 300s, compared with the initial temperature, the standard Marshall sample (+21.4℃), the Marshall sample coated with the asphalt pavement anti-icing coating 6 (+26℃), and the Marshall sample coated with the photothermal hydrophobic coating 4 (+34.3℃) increased significantly. The results show that after adding carbon nanotubes, the sensitivity of the coating to the microwave thermal effect is significantly improved. The Marshall samples all showed a higher temperature difference in a shorter heating time, and the heating rate also showed an upward trend with the increase of heating time.

[0077] The microwave deicing performance of the asphalt pavement anti-icing coating 4 prepared in Example 2 was tested, and the specific experimental steps are as follows.

[0078] At -20°C, a uniform 20 mm thick ice layer was prepared on the surface of the Marshall specimens coated with the asphalt pavement anti-icing coating 4, the Marshall specimens coated with the asphalt pavement anti-icing coating 6 (Comparative Example 5), and the Marshall specimens without coating. At room temperature (20°C), the Marshall specimens were placed in a microwave oven with a constant power of 160 W and a frequency of 2.45 GHz and heated until de-iced, and the de-icing time was recorded.

[0079] In the Marshall sample microwave deicing experiment, there were significant differences in the deicing time of samples treated with different coatings. Specifically, the Marshall specimen coated with the asphalt pavement anti-icing coating 4 only required 2 minutes of microwave heating to completely remove the ice on its surface. In contrast, the Marshall specimen coated with the asphalt pavement anti-icing coating 6 required 9 minutes to achieve a similar ice melting effect, while the standard Marshall sample required 11 minutes. This phenomenon highlights the obvious microwave absorption and heating ability of the photothermal hydrophobic coating 4 during the heating process, which accelerates the separation of ice from the sample surface. Carbon nanotubes enhance the high microwave absorption and thermal conductivity of the coating, effectively converting microwave energy into thermal energy quickly, thereby increasing the melting rate of ice.

[0080] The asphalt pavement anti-icing coating 4 prepared in this Example 2 was tested for its anti-ultraviolet aging performance using a GM-UV-1140 ultraviolet aging test box, and the results are as follows.

[0081] Table 4 Comparison of the test results of different properties of asphalt pavement anti-icing coatings before and after UV aging

[0082]

[0083] At a low temperature of -10°C, the photothermal response of the asphalt pavement anti-icing coating 4 decreases with the increase of UV aging time. Among them, after 24h, 48h, and 72h of UV aging, under near-infrared light irradiation, the temperature rise of the coating reached 14.7°C, 14.8°C, and 14.2°C within 60s, respectively. Specifically, after 72 hours of UV aging, the final temperature rise of the asphalt pavement anti-icing coating 4 was only 0.4°C lower than that of the coating that had not been treated with UVc, indicating that its photothermal heating effect was hardly significantly affected by the UV aging time.

[0084] The microwave effect of asphalt pavement anti-icing coating 4 after UV aging for different times was tested at room temperature (20°C). The initial temperature was always around 19.4°C. After microwave aging for 300s, the surface temperature of the specimens rose to 55.2°C, 54.8°C, and 55.1°C, respectively. The results showed that the microwave heating rate of the specimen after UV aging for 72 hours was not significantly different from that before UV aging, and the final temperature only dropped by 0.5°C.

[0085] The contact angle of water droplets on the surface of asphalt pavement anti-icing coating 4 decreased from 151.42° to 149.88° after aging for 24 hours, decreased to 148.18° after 48 hours, and further decreased to 147.36° after 72 hours. The contact angle of the coating gradually decreased with the extension of UV aging time, but the decrease was very small.

[0086] The above experimental results show that the asphalt pavement anti-icing coating 4 has satisfactory durability after UV aging. The effect on the performance of the coating is relatively small, highlighting its resilience to UV aging.

[0087] For matters not mentioned above, the prior art applies.

[0088] Although some specific embodiments of the present invention have been described in detail through examples, those skilled in the art should understand that the above examples are for illustration only and are not intended to limit the scope of the present invention. Those skilled in the art to which the present invention belongs may make various modifications or supplements to the specific embodiments described or replace them in a similar manner, but they will not deviate from the direction of the present invention or exceed the scope defined by the attached claims. Those skilled in the art should understand that any modifications, equivalent substitutions, improvements, etc. made to the above embodiments based on the technical essence of the present invention should be included in the protection scope of the present invention.

Claims

1. A photothermal hydrophobic coating, characterized in that: It includes the following raw materials in parts by weight: 1-1.5 parts of multi-walled carbon nanotubes, 3-4 parts of titanium dioxide, 6-7 parts of lauric acid, and 100 parts of anhydrous ethanol.

2. A photothermal hydrophobic coating as claimed in claim 1, characterized in that, The multi-walled carbon nanotube has an inner diameter of 3-5 nm, an outer diameter of 8-15 nm, and a length of 3-12 μm.

3. A photothermal hydrophobic coating as claimed in claim 1, characterized in that, The average particle size of the titanium dioxide is 50nm and the specific surface area is 60-70m 2 / g.

4. A photothermal hydrophobic coating as claimed in claim 1, characterized in that, The pH of the lauric acid is 6.5-7 and the density is 1.05 g / cm 3 .

5. A photothermal hydrophobic coating as claimed in claim 1, characterized in that, The mass ratio of the multi-walled carbon nanotubes, titanium dioxide and lauric acid is 1:3:

5.

6. An application of the photothermal hydrophobic coating according to any one of claims 1 to 5 on an asphalt pavement, characterized in that: The multi-walled carbon nanotubes, titanium dioxide and lauric acid are weighed and uniformly mixed with anhydrous ethanol to obtain the coating, and then the coating is sprayed on the asphalt cured layer of the road surface to form an anti-icing coating.

7. The use according to claim 6, characterized in that: The coating spraying volume is 90-110mL / m 2 .

8. The use according to claim 6, characterized in that: The asphalt solidification layer is formed by coating the emulsified asphalt on the roadbed and solidifying it.

9. The use according to claim 6, characterized in that: The preparation method of emulsified asphalt is as follows: water, non-ionic emulsifier and anhydrous calcium chloride are mixed to prepare soap solution, and the base asphalt is preheated to 100-120°C and then mixed and stirred with the soap solution.

10. The use according to claim 9, characterized in that: The mass ratio of base asphalt, water, nonionic emulsifier and anhydrous calcium chloride is 100:70:3:0.1.

Citation Information

Patent Citations

  • Emulsified asphalt for ballastless track cement emulsified asphalt mortar and preparation method of emulsified asphalt

    CN104277462A

  • Super-hydrophobic coating for asphalt pavement and preparation method thereof

    CN113265193A

  • Preparation method of super-hydrophobic wear-resistant coating containing buffer structure

    CN114535022A

  • Acrylic acid super-hydrophobic coating capable of being heated by microwaves and preparation method of acrylic acid super-hydrophobic coating

    CN115746639A

  • Super-hydrophobic coating with photo-thermal performance and preparation method thereof

    CN118791915A

Cited By

  • Multifunctional composite coating of OSB (oriented strand board) and preparation method of multifunctional composite coating

    CN121537883A